Protocol for multiplexed RNAscope-based imaging of mRNAs in whole-mount adult Drosophila brains - Meilin Wu; Vanessa Lambatan; Peng Guo; William J. Joiner (STAR Protocols)
Summary: Visualizing the expression of mRNAs using traditional in situ hybridization is often hampered by obstacles including weak signal, high background, and poor probe specificity. Here, we present a protocol utilizing RNAscope (ACD) to overcome these obstacles and detect multiple types of mRNAs simultaneously in whole-mount adult Drosophila brains. We further describe how mRNAs can be reliably quantified in any cells that can be targeted by common binary expression systems such as Gal4/UAS and labeled by immunohistochemistry.For complete details on the use and execution of this protocol, please refer to De et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.